Dietary β-mannanase decreases cloacal temperature of broiler chickens under hot conditions without affecting growth performance - Yang, Tae Sung; Kim, Moon Chan; Martinez Pitargue, Franco; Choi, Hyeon Seok; Kil, Dong Yong (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: High amounts of nonstarch polysaccharides in the diet may increase the amounts of fermentative materials in the hindgut, leading to an increase in fermentative heat production. Dietary β-mannanase is reported to decrease antinutritional effects of β-mannans, such as the potential increase of body heat; however, its efficacy on broiler chickens raised under hot climatic conditions has not been investigated. Objective: To investigate the effects of dietary β-mannanase on growth performance, cloacal temperature, relative lymphoid organ weight, and blood characteristics of broiler chickens raised under hot climatic conditions. Methods: A total of 1,701 1-day-old Ross 308 broiler chickens were randomly allotted to one of three dietary treatments with nine replicates. A basal diet was prepared and added with β-mannanase at 0.05 or 0.10% inclusion levels. The experiment was conducted for 30 days. Average room temperature was 28.8 ± 1.74 ̊C and average relative humidity (RH) was 76.1 ± 11.49% during the experiment. Results: Growth performance of broiler chickens raised under hot climatic conditions was not affected by β-mannanase inclusion. Cloacal temperature decreased at the end of experiment (linear, p<0.05) with increasing inclusion levels of dietary β-mannanase. Increasing inclusion levels of β-mannanase tended to increase (linear, p=0.076) the relative weight of thymus, but had no effects on the relative weight of spleen and bursa of Fabricius. Blood characteristics were not influenced by dietary β-mannanase. Conclusion: Increasing inclusion levels of β-mannanase decrease cloacal temperature; however, it does not directly influence growth performance nor alleviates the heat stress of broiler chickens raised under hot climatic conditions.